Contributions of lexical tone to Mandarin sentence recognition in hearing-impaired listeners under noisy conditions - Li, Nan (J Acoust Soc Am, 2019)
Mandarin sentence recognition using natural-tone and flat-tone sentences was tested in 22 subjects with sensorineural hearing loss (SNHL) and 25 listeners with normal hearing (NH) in quiet, speech-shaped noise, and two-talker-babble conditions. While little effects of flat tones on sentence recognition were seen in the NH listeners when the signal-to-noise ratio (SNR) was ≥0 dB, the SNHL listeners showed decreases in flat-tone-sentence recognition in quiet and at +5-dB SNR. Such declined performance was correlated with their degrees of hearing loss. Lexical tone contributes greatly to sentence recognition in hearing-impaired listeners in both quiet and in noise listening conditions.